Personal commentary - Riley, D (Oxford Institute for Energy Studies, 2006)
Not so long ago – as recently as the 1990s, the world was ‘awash with oil’. Today, while oil reserves remain ample, production is hard put to keep pace with demand. True, there is a lot of political uncertainty to jack up the price of crude oil, through threats on capacity to produce, transport and refine it, but there is increasing recognition that much of the current price hike is demand induced. China’s role deserves our attention.